Some Features of Hemorrhagic Syndrome in Chronic Diffuse Liver Diseases - Zumrad Ch. Kurbonova1, Shaira A. Babadjanova2, Zulfiya S. Islamova3, Abdumurat S. Babadjanov4, Nargi (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective of the Study: To characterize the hemorrhagic syndrome in patients with chronic hepatitis andliver cirrhosis of viral cause.Materials and Method: 80 patients with liver cirrhosis of viral cause have been studied, 20 patients withliver cirrhosis of non-viral cause and 62 patients with chronic viral hepatitis.Results of the Study: Hemorrhagic syndrome was pronounced in patients with liver cirrhosis of viral cause,and much less pronounced in the group of patients with liver cirrhosis of non-viral cause. In patients withchronic viral hepatitis B and C, bleeding symptoms were much less common.Conclusions: Severe hemorrhagic syndrome with liver cirrhosis of viral cause requires a detailed study ofcoagulation and vascular-platelet hemostasis for the prevention and treatment of bleeding.